Hole Transfer Layer Engineering for CdTe Nanocrystal Photovoltaics with Improved Efficiency - Yasi Jiang (Nanomaterials, 2020)
Interface engineering has led to significant progress in solution-processed CdTe nanocrystal (NC) solar cells in recent years. High performance solar cells can be fabricated by introducing a hole transfer layer (HTL) between CdTe and a back contact electrode to reduce carrier recombination by forming interfacial dipole effect at the interface. Here, we report the usage of a commercial product 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro) as a hole transfer layer to facilitate the hole collecting for CdTe nanocrystal solar cells. It is found that heat treatment on the hole transfer layer has significant influence on the NC solar cells performance. The Jsc, Voc, and power conversion efficiency (PCE) of NC solar cells are simultaneously increased due to the decreased contact resistance and enhanced built-in electric field. We demonstrate solar cells that achieve a high PCE of 8.34% for solution-processed CdTe NC solar cells with an inverted structure by further optimizing the HTL annealing temperature, which is among the highest value in CdTe NC solar cells with the inverted structure.